Selection of Filtering Method for Accurate Bunch Length Measurement at Synchrotron Radiation Source - Jain, Monika; Saxena, Rahul (International Journal of Engineering and Technology, 2018)
The measurement of the object parameters present in an image is a difficult task because the image not only contains the objects information but a noise is also associated with the image. The type of noise present in the image depends upon the various parameters like sensors, transmission signal and surrounding conditions. In this paper, we are studying the special type of images of electronic particles (visible light of electromagnetic radiations captured at different beam currents produced by synchrotron radiation source), these images contain visible part information of radiation called bunch. In these images our main aim is to calculate the bunch parameters but due to different light condition and other factors the captured images of bunch is found to be noisy and it causes great loss of bunch information in the image. The image filtering in those kinds of images should be done in such a way that the filter should identify the noisy pixels present in the image and remove them while retaining the original information of the bunch image, for precise measurement of this bunch present in an image appropriate filtering method and filter size is chosen. This paper discusses the test results of bunch parameters by applying various filters and appropriate filter is chosen based upon the measured test results.Â Â Â